(untitled) (Journal of Educational Sciences, 2017)
We conducted the experiment, analysis of the state of preparation for General physics students in secondary schools shows low level of their readiness for the solution of educational tasks in the learning process of razdel quantum physics. Over half of the students experience difficulties in self-application of physical knowledge to the explanation of physical phenomena, processes, to solve tasks when working with physical hardware. Our proposed learning methodology section of quantum physics in school is aimed at formation of professional competence of future teachers of physics and solve the above difficulties among students. In this regard, the International Kazakh-Turkish University named after K. A. Yassawi pays great attention to the development of technical bases the use of new technologies and poper methods of teaching of quantum physics in the preparation of future teachers and develop electronic resources for use in teaching quantum physics. Using computer models of the experiments and demonstrations you can compensate the lack of equipment in the physical laboratory and thus, to teach students independently to extract physical knowledge in the course of physical experiments on virtual models, that is, there is a real possibility of formation of students professional competence and increasing cognitive activity in physics, in particular quantum physics. Key words: future teachers of physics, pupils, quantum physics, professional competence, methodology.